Social Tapestry of Economic Life from Mark Granovetter’s Idea of Social Embeddedness - Kashi Nath Khanal,; Tek Nath Subedi, (Journal of Development Review, 2025)
This essay challenges the "over-socialized" perspective of classical economic sociologists and the "under-socialized" conception of classical economists as "homo economicus," contending that economic actions are deeply rooted in society. In doing this, I have fully relied on Mark Granovetter's idea of social embeddedness, which critiques both the over-socialized view of people as merely puppets of normative social conduct proposed by some sociological theories and the under-socialized view of atomistic rational actors frequently promoted in economics. Rather, economic agents are thought of as balanced actors who make decisions and act in certain ways, either through generalized morality or the abstract logic of the market or through continuous, tangible social relationships, trust, and network structure. Taking inspiration from earlier thinkers like Karl Polanyi, this essay broadens its scope to explore the socio-economic landscape of Nepal in depth. It vividly illustrates how economic activities are intricately linked to kinship, ethnicity, power dynamics, and cultural obligations—ranging from Dhukuti (ROSCA) to Guthi systems, remittances, community forestry, and the complex networks of caste and patron-client relationships. The essay delves into the nuances of embeddedness, including its potential downsides in addition to the methodological challenges of its study. It wraps up with a strong assertion that economic life is inherently social, advocating for a holistic perspective that merges economic rationalities with the social fabric shaped by human interactions and structures, which is essential for both accurate analyses and effective interventions.